2017
DOI: 10.7150/ijbs.16404
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Alpha 7 Nicotinic Acetylcholine Receptor Activation on Critical Illness and Its Mechanism

Abstract: Critical illnesses and injuries are recognized as major threats to human health, and they are usually accompanied by uncontrolled inflammation and dysfunction of immune response. The alpha 7 nicotinic acetylcholine receptor (α7nAchR), which is a primary receptor of cholinergic anti-inflammatory pathway (CAP), exhibits great benefits for critical ill conditions. It is composed of 5 identical α7 subunits that form a central pore with high permeability for calcium. This putative structure is closely associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 133 publications
0
37
0
Order By: Relevance
“…The dorsal motor nucleus is activated after interconnecting with nucleus tractus solitarius, and further drives the excitation of efferent vagus nerve for Ach release [102,103]. The anti-inflammatory effects of CAP are achieved after activation of α7nAchR, which disrupts activation of NF-κB and inflammasomes by promoting phosphorylation of the Janus kinase 2 (JAK2)-signal transducer and activator of transcription 3 (STAT3) pathway, inhibiting the TLR4-myeloid differentiation factor 88 (MyD88)-interleukin-1 receptorassociated kinase (IRAK) cascade and the release of mitochondrial DNA [104][105][106][107]. It has been reported that activation of α7nAchR is capable of blocking activation and entry of NF-κB via interfering phosphorylation of inhibitor κB (IκB) [108,109].…”
Section: Cholinergic Anti-inflammatory Pathwaymentioning
confidence: 99%
“…The dorsal motor nucleus is activated after interconnecting with nucleus tractus solitarius, and further drives the excitation of efferent vagus nerve for Ach release [102,103]. The anti-inflammatory effects of CAP are achieved after activation of α7nAchR, which disrupts activation of NF-κB and inflammasomes by promoting phosphorylation of the Janus kinase 2 (JAK2)-signal transducer and activator of transcription 3 (STAT3) pathway, inhibiting the TLR4-myeloid differentiation factor 88 (MyD88)-interleukin-1 receptorassociated kinase (IRAK) cascade and the release of mitochondrial DNA [104][105][106][107]. It has been reported that activation of α7nAchR is capable of blocking activation and entry of NF-κB via interfering phosphorylation of inhibitor κB (IκB) [108,109].…”
Section: Cholinergic Anti-inflammatory Pathwaymentioning
confidence: 99%
“…GTS-21, a classic cholinergic agonist, can bind to the α7 subunit of the nicotinic acetylcholine receptor (α7nAChR) of inflammatory cells to induce an anti-inflammatory response [ 17 ]. A previous study showed that the CAP is involved in the reduction of inflammation in experimental sepsis, acute lung injury, ischemia/reperfusion injury, and pancreatitis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it has been shown that acetylcholine (ACh) released from nerve fibers may have anti-inflammatory effects inasmuch as it suppresses cells of the immune system through activation of α7 nicotinic acetylcholine receptor (α7nAChR). In fact, stimulation of α7nAChR activates intracellular signaling pathways that culminate in the inhibition of NF-kβ factor in immune cells, thereby suppressing the release of proinflammatory cytokines 13,14 . This mechanism has been referred to in the literature as "cholinergic anti-inflammatory pathway".…”
mentioning
confidence: 99%